2004
DOI: 10.1111/j.1348-0421.2004.tb03477.x
|View full text |Cite
|
Sign up to set email alerts
|

The Anthracycline Antitumor Agents Doxorubicin and Daunorubicin Reduce the Activity of Candida albicans Phospholipase B

Abstract: A pathogenic yeast, Candida albicans, causes life‐threatening infection in immunocompromised patients. Inhibiting the production or release of phospholipase B by C. albicans should reduce direct host cell damage, and inhibit the release of eicosanoids from cells of this microorganism. Of the antitumor agents tested, doxorubicin and daunorubicin inhibited the activity of phospholipase B, and prostaglandin production by C. albicans. These two agents have the potential to inhibit the activity of C. albicans phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The principal PL activity of C. albicans detected in the supernatants of the cultures is due to PL B activity. Activity of PL B can be reduced by anthracycline antitumour agents doxorubicin and daunorubicin 98 and by brief exposure to antimycotics 99 . By using a PCR‐based approach on the basis of degenerated primers, two PLB genes were cloned 92, 95, 96 .…”
Section: Extracellular and Intracellular Phospholipases Of C Albicansmentioning
confidence: 99%
“…The principal PL activity of C. albicans detected in the supernatants of the cultures is due to PL B activity. Activity of PL B can be reduced by anthracycline antitumour agents doxorubicin and daunorubicin 98 and by brief exposure to antimycotics 99 . By using a PCR‐based approach on the basis of degenerated primers, two PLB genes were cloned 92, 95, 96 .…”
Section: Extracellular and Intracellular Phospholipases Of C Albicansmentioning
confidence: 99%
“…DOX is an effective anthracycline anti-cancer drug, widely used in cancer therapy for various types of cancers, (Arai et al 2004;Mattioli et al 2004) and usage of DOX has been restricted due to its side effects which affects quality of life of patients (Arai et al 2004;Havsteen et al 1985;Hudis and Schmitz 2004;Kesik et al 2010). Clinical studies have shown that patients treated with DOX reportedly suffer from cardiac related problems (Ho et al 2010;Panjrath and Jain 2006;Sparano et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, cellular mechanisms of developed cardiac toxicity is not well studied. Doxorubicin (DOX) is a strong anti-cancer drug, which is used to treat variety of malignant tumors (Arai et al 2004;Mattioli et al 2004). DOX induced cardiac and muscle toxicity in nondiabetic patients and animal models is well documented (Alhowail et al 2019;Gorelik et al 2003;Hudis and Schmitz 2004;Johnson and Singla 2018;Pal et al 2012;Rudzinski et al 2007;Singal and Iliskovic 1998;Singla et al 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipase B and secretory aspartyl protease are major virulence factors. Of these, anthracycline compounds inhibit the activity of phospholipase B in a dose-dependent manner [21]. Doxorubicin also inhibits the replication of HIV [22], herpes simplex virus [23], dengue virus, and yellow fever virus [24].…”
Section: Discussionmentioning
confidence: 99%